Pentahelix Collaboration in Implementing the Digital Village Program in the Era of Ridwan Kamil's Leadership, Governor of West Java Province - Ranti Febrianti; Gita Mawarni; Rasya Firrizqy; Farhan Herlambang (Social Impact Journal, 2023)
This paper aims to analyze the leadership role of Governor Ridwan Kamil in the West Java Government Era in implementing the Digital Village Program. The analysis tool used is using a modelpentahelix which consists of five elements, namely the Government (government), Public (society), Academy (academician), Businessmen (businessmen), and Media (media). The discussion is carried out by analyzing the descriptions of the five roles in the Penta helix model. The method used in this study uses the literature study method by utilizing secondary data in the form of news archives and the results of previous research in the form of journal articles. The goal to be achieved is to describe Ridwan Kamil's leadership role in the digital village program for the West Java Government so that it can build a digital-based village from various aspects. The findings in this study are that Ridwan Kamil's leadership role for West Java Government in implementing the digital village program is optimal by involving related roles such as government, community, academics, business actors, and media for village change in West Java. However, there are still obstacles to implementing the digital village program in related villages.